2021
DOI: 10.1177/00469580211028579
|View full text |Cite
|
Sign up to set email alerts
|

Health System Governance for the Integration of Mental Health Services into Primary Health Care in the Sub-Saharan Africa and South Asia Region: A Systematic Review

Abstract: Governance has been highlighted as an important building block underpinning the process of mental health integration into primary healthcare. This qualitative systematic review aims to identify the governance issues faced by countries in the Sub-Saharan Africa and South Asia Region in the implementation of integrated primary mental healthcare. PRISMA guideline was used to conduct a systematic search of relevant studies from 4 online databases that were filtered according to inclusion and exclusion criteria. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Clinical governance facilitates the adherence of clinical principals, organizational priorities, and standards. Yet there is a paucity of research examining clinical governance as it pertains to the integration of mental health in primary care [ 45 ]. Findings from this study suggests that clinical governance is an integral organizational structure that can facilitate the uptake of mental health as a priority in interprofessional primary care teams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical governance facilitates the adherence of clinical principals, organizational priorities, and standards. Yet there is a paucity of research examining clinical governance as it pertains to the integration of mental health in primary care [ 45 ]. Findings from this study suggests that clinical governance is an integral organizational structure that can facilitate the uptake of mental health as a priority in interprofessional primary care teams.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, there has been a spike in mental health care demands, which along with the health human resources crisis, highlights the immediate need to attract and retain mental health professionals in primary care [ 47 , 80 ]. A systematic review conducted by Rahim et al found that a shortage of trained health professionals—and difficulties with recruitment and retention—significantly affected the extent to which mental health was integrated into primary care [ 45 ]. Rural and urban primary care teams are facing various challenges in the human resources crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, situation-specific governance and advocacy could determine the right balance between the potential for benefit and potential for harm in different settings. Solid governance is vital for strong MMH care systems in a country or region, and our study is not unique in highlighting that policy makers and programme specialists need to be more aware of mental health issues and improved governance needs to be set up to facilitate effective and safe services [39]. There are numerous, well-documented ways forward, including task-shifting, which could help strengthen services in the short and medium terms [40].…”
Section: Benefits and Risksmentioning
confidence: 97%
“…The researcher summarized the selected articles to answer the research question of this study. To ease the process of summarizing the articles, data extraction was conducted in Microsoft Excel and tabulated into Summary Matrix (Appendix A), which includes the name of author, year of publication, document type, research design, keywords, type of mathematics learning disabilities and educational intervention (Rahim et al, 2021). Subsequently, Table 5 were constructed to make the researchers to have a quick review on the two important data which is the type of mathematics learning disability and the educational intervention that were discussed among the articles.…”
Section: Summarizing the Evidencementioning
confidence: 99%